2021
DOI: 10.1101/2021.04.12.439451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynein activation in vivo is regulated by the nucleotide states of its AAA3 domain

Abstract: Cytoplasmic dynein is activated by cargo adapters, dynactin, and LIS1. However, it is unclear whether there are additional regulations for coordinating cargo binding and dynein activation. Here we found that a dynein AAA4 arginine-finger mutation in Aspergillus nidulans bypasses the requirement of LIS1 for dynein activation driven by the early endosomal adapter HookA. As AAA4 arginine-finger is implicated in AAA3 ATP hydrolysis, we examined AAA3 mutants defective in ATP binding and hydrolysis respectively. Ast… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 156 publications
(326 reference statements)
1
4
0
Order By: Relevance
“…A similar pathway for dynein regulation may exist in other organisms, including mammalian cells (Figure 8B), and related mechanisms have recently been proposed (Markus et al, 2020;Qiu et al, 2021). Our work shows that both the sitering and sitestalk Lis1 binding sites on dynein are important for the formation of active human dyneindynactin-activating adaptor complexes containing either the Hook3 or BicD2 activating adaptors.…”
Section: Discussionsupporting
confidence: 81%
“…A similar pathway for dynein regulation may exist in other organisms, including mammalian cells (Figure 8B), and related mechanisms have recently been proposed (Markus et al, 2020;Qiu et al, 2021). Our work shows that both the sitering and sitestalk Lis1 binding sites on dynein are important for the formation of active human dyneindynactin-activating adaptor complexes containing either the Hook3 or BicD2 activating adaptors.…”
Section: Discussionsupporting
confidence: 81%
“…While dynein's microtubule binding domain is not required to reach the cortex (Lammers and Markus, 2015), our data suggest some role for microtubule binding in this process. Assembling active dynein-dynactinactivating adaptor complexes likely involves multiple steps and the many in vitro phenotypes described for Lis1's regulation of dynein, such as the nucleotide-specific affects at AAA3 (DeSantis et al, 2017;Qiu et al, 2021), may be providing mechanistic hints about these steps.…”
Section: Discussionmentioning
confidence: 99%
“…Genetically, mutations that link nucleotide hydrolysis at AAA3 to Lis1 have also been reported (Qiu et al, 2021;Willins et al, 1997;Zhuang et al, 2007). While it remains to be determined how the readouts described above or other in vitro readouts of Lis1 regulation of dynein (Baumbach et al, 2017;Gutierrez et al, 2017;Jha et al, 2017;Marzo et al, 2020;Wang et al, 2013) relate to Lis1's in vivo function, they serve as powerful tools to test structure/ function predictions (DeSantis et al, 2017;Toropova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that AAA1 is the main site for ATPase activity 42,45,47 , with AAA3 and AAA4 playing regulatory roles during motility and force production [48][49][50][51] . Previous studies have also found that the nucleotide state of AAA3 may play a direct role in modulating dynein-Pac1 affinity 52,53 . To determine whether ATP binding or hydrolysis at AAA1, 3 or 4 might affect the ability of dyneinMOTOR MT-B or dyneinMOTOR MT-U , we mutated either Walker A or Walker B ("WA", or "WB"; responsible for ATP binding and hydrolysis, respectively) in AAA1, 3 and 4, and assessed the extent of their plus end binding.…”
Section: The Nucleotide-bound State Of Dynein Affects Its Affinity Fo...mentioning
confidence: 96%